Fermentation technology and quality of sauce prepared from rice dreg protein. Issue 3 (29th June 2015) - Yuan, Jianglan; Zhong, Wenxiu; Jin, Yan; Lin, Can; Kang, Xu; Deng, Chong
<x xml:space="preserve">Abstract</x> Fermented sauce, from rice dreg protein (RDP) instead of soybean, has unique advantages. In the present paper, the fermentation technology of RDP sauce was studied. Amino nitrogen, reducing sugar, soluble protein and colour indicators, as well as the quality of three kinds of RDP sauce fermented under different conditions, were analysed. The results suggest that an optimized fermentation technology is the addition of 2.4 times salty solution into koji, to obtain a 13% salt concentration in the sauce mash, and then fermentation at ~35°C. RDP sauce that had an addition of 0.01% Zygosaccharomyces rouxii in the fermentation stage gave a good quality RDP sauce. The RDP sauce content of amino nitrogen and reducing sugar, with 0.01% Z. rouxii, was 0.98 and 4.57 g/100 mL respectively, and the corresponding sensory quality was better than in the samples produced without Z. rouxii. It was concluded that RDP can be utilized to produce a high‐quality sauce. Copyright © 2015 The Institute of Brewing & Distilling